Effect of the Middle East peace process on pan Arab tourism industries - Ladki, Said M. (2001)
In a perfect world, countries in the Middle East would be stable politically, united economically, and surrounded by peace-loving responsible neighbors advocating the flow of tourism. People would not be dying because of war, and tourists and investors would not be apprehensive of the entire region. Before the war, Lebanon was a central tourist destination for the Arab world and beyond. Today, in the aftermath of a 16-year civil war, Lebanon is struggling to recover. To say the least, this is not a perfect world. This article will discuss the Peace Process and its effect on Pan Arab tourism industries.